2007
DOI: 10.1016/j.ydbio.2007.01.034
|View full text |Cite
|
Sign up to set email alerts
|

The characterization of zebrafish antimorphic mib alleles reveals that Mib and Mind bomb-2 (Mib2) function redundantly

Abstract: Both mind bomb (mib) and mind bomb-2 (mib2) encode RING E3 ubiquitin ligases that promote Delta ubiquitylation and endocytosis in Notch activation. Detailed morphological and molecular examinations revealed that zebrafish mib(ta52b) (missense mutation in the C-terminal RING Finger (RF), M1013R) and mib(m132) (nonsense mutation resulting in a truncated protein that loses all three RFs, C785stop) are strong and weak antimorphic alleles, respectively, compared to the null allele, mib(tfi91) (nonsense mutation res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 82 publications
8
56
0
1
Order By: Relevance
“…Previous studies have suggested that whereas DeltaD is a substrate for Mib1, DeltaC, expressed in a small subset of neuronal progenitors (Smithers et al, 2000), is a substrate for both Mib1 and its paralog, Mib2 (Zhang et al, 2007a;Zhang et al, 2007b). Consistent with the specific requirement of Mib1 for DeltaD ubiquitylation, DeltaD is on the cell surface in both mib1 ta52b and mib1 m178 embryos ( Fig.…”
Section: Deltac Endocytosis Is Regulated Differently From Deltad and supporting
confidence: 77%
See 1 more Smart Citation
“…Previous studies have suggested that whereas DeltaD is a substrate for Mib1, DeltaC, expressed in a small subset of neuronal progenitors (Smithers et al, 2000), is a substrate for both Mib1 and its paralog, Mib2 (Zhang et al, 2007a;Zhang et al, 2007b). Consistent with the specific requirement of Mib1 for DeltaD ubiquitylation, DeltaD is on the cell surface in both mib1 ta52b and mib1 m178 embryos ( Fig.…”
Section: Deltac Endocytosis Is Regulated Differently From Deltad and supporting
confidence: 77%
“…The mib1 m178 allele encodes a truncated Mib1 m178 protein that lacks the third RING domain essential for its ubiquitin ligase function (Itoh et al, 2003). Nonsense-mediated degradation of mib1 m178 transcript significantly reduces the amounts of the mutant protein and its phenotype is like that of a null mutant (Zhang et al, 2007b). By contrast, the mib1 ta52b transcript, which is relatively stable, encodes a Met to Arg substitution in the third RING domain.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, RBP-J deletion in FOXD1 cells (mural and renin cell progenitors) causes renal developmental defects and a severe reduction in renin expression (46). The requirement of Notch signaling for ren expression in developing fish was assessed in Notch signalingimpaired mib ta52b mutants, which are phenotypically the strongest of mutant mib alleles (82). The ubiquitin ligase mib is essential for the Delta-mediated activation of the transmembrane Notch receptor in target cells (29).…”
Section: Notch Signaling and Renin Expression Mammalian Renin Cells mentioning
confidence: 99%
“…The treatment induced looped tail and impaired somitogenesis (supplementary material Fig. S3A,B), developmental defects that result from reduced Notch signalling (Zhang et al, 2007). Expression of the Notch target her6 and her15 was also reduced (supplementary material Fig.…”
Section: Notch Signalling Inhibition Reduces Proliferation and Impairmentioning
confidence: 99%